MANAJEMEN KOPERASI ( STUDI KASUS PELAYANAN PADA KOPERASI SERBA USAHA SENTOSA IKAT DI KOTA BUKITTINGGI) - Hasbi Ash Shiddiqi; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Based on the background found a phenomenon that occurs in the field, namely the service obtained by members of the cooperative from the service and cooperative management less satisfying members of the cooperative, cooperative management does not accept aspirations and suggestions from members of the cooperative both in terms of cooperative activities, cooperative members also do not get information from cooperative management about activities carried out in cooperative savings and loans. The type used in this study is qualitative with descriptive survey techniques. The location of this study was conducted at the Sentosa Ikat Multipurpose Cooperative in the City of Bukittinggi. Research Results Cooperation Management Fields Case Study of the Sentosa Ikat Multipurpose Cooperative in the City of Bukittinggi can be seen from the results of research interviews, that the policy targets were not achieved because cooperative members were not satisfied with achieving welfare members of cooperatives, official resources and management of cooperatives have been sufficient to provide services to members of cooperatives and it is different from the opinions of members who receive services from the cooperative management. Keywords: Management, Cooperative, Service